Two new species of callanthiid fishes of the genus Grammatonotus (Percoidei: Callanthiidae) from Pohnpei, western Pacific - Anderson, William D., Jr.; Johnson, G. David (Zootaxa, 2017)
In late July/early August 2015, ichthyologists from the Bishop Museum collecting fishes off Pohnpei in the Caroline Islands group, western Pacific Ocean, obtained specimens of two undescribed species of Grammatonotus. One of the new species, G. xanthostigma, closely resembles the recently described G. brianne, differing most strikingly in the shape of the caudal fin. The other, G. pelipel, is distinctive in having the following combination of characters: disjunct lateral line, barred pattern of coloration (most distinctive in small individuals), and caudal fin truncate to slightly emarginate in small specimens, but with upper and lower lobes produced in largest example known. Herein we provide characters that distinguish callanthiids from other percoids and that distinguish Grammatonotus from Callanthias, the other genus in the family Callanthiidae, along with descriptions of the new species.